2017
DOI: 10.1111/aogs.13130
|View full text |Cite
|
Sign up to set email alerts
|

Impact of uterine balloon tamponade on the use of invasive procedures in severe postpartum hemorrhage

Abstract: Although the efficacy of tamponade should be viewed in the light of its widespread use, our findings confirm that tamponade significantly reduces the need for interventional radiology or surgery for postpartum hemorrhage treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
25
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 27 publications
5
25
1
1
Order By: Relevance
“…Further, results of both studies suggest possible harm. In contrast, studies conducted in high‐resource settings show that UBT introduction was associated with a decline in invasive procedures for PPH . These conflicting findings may be explained by differences in study contexts, as both our study and the Dumont trial were conducted in LMIC where the clinical benefit of UBT may be attenuated by the lack of system capacity to address obstetric emergencies such as refractory PPH adequately.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Further, results of both studies suggest possible harm. In contrast, studies conducted in high‐resource settings show that UBT introduction was associated with a decline in invasive procedures for PPH . These conflicting findings may be explained by differences in study contexts, as both our study and the Dumont trial were conducted in LMIC where the clinical benefit of UBT may be attenuated by the lack of system capacity to address obstetric emergencies such as refractory PPH adequately.…”
Section: Discussioncontrasting
confidence: 60%
“…Observational and before‐and‐after studies from high‐resource settings show a decline in invasive procedures for PPH (i.e. surgical intervention or uterine artery embolisation) associated with UBT introduction . Most research on UBT in high‐resource settings has evaluated costly devices such as the Bakri balloon, but a similar effect can be achieved using the low‐cost alternative of tying a condom to the end of a urinary catheter .…”
Section: Introductionmentioning
confidence: 99%
“…Due to its simplicity and relatively noninvasive nature, IUBT has been incorporated into standard protocols for the management of severe PPH as a second‐line conservative surgical procedure . Recent data have shown that the increasing use of a balloon tamponade was associated with a reduction in the need for more invasive procedures, such as radiological uterine artery embolization or compression sutures, as well as the incidence of peripartum hysterectomy …”
Section: Introductionmentioning
confidence: 99%
“…Laas et al 9 reported that introduction of balloon tamponade into the standard treatment algorithm for PPH resulted in a large and significant decrease in the rates of arterial embolization and ligation procedures as well as the use of compression sutures. These findings were subsequently confirmed by Gauchotte et al, 23 who additionally showed a decrease in the need for operative hysterectomy following the introduction of balloon tamponade in PPH management.…”
Section: Discussionmentioning
confidence: 58%